Shade-Grown Slavery : The Lives of Slaves on Coffee Plantations in Cuba - Van Norman, William C. (William Chisholm), 1957- (Book collections on Project MUSE., 2013)
This book explores the lives of enslaved Africans on Cuban coffee plantations and shows how they were able to maintain and transform their cultural traditions in spite of the harshness of slavery. -- Provided by publisher.